Vasa previa: A rare obstetric complication–A case series and a literature review. Issue 3 (22nd March 2022) - Degirmenci, Yaman; Steetskamp, Joscha; Macchiella, Doris; Hasenburg, Annbalou; Hasenburg, Annette
Abstract: Vasa previa is a rare condition. However, since the increase in assisted reproductive technologies (ARTs), clinicians are more frequently confronted with this complication. In this study, we present five cases of vasa previa prenatally diagnosed from a tertiary referral hospital with approximately 2000 births yearly. Abstract : Accurate prenatal diagnosis and sufficient management before the onset of labor improve the outcome of pregnancies complicated with vasa previa.